Generalizing the compressible pairwise interaction extended point-particle model - Hsiao, Smyther S.; Ouellet, Frederick; Regele, Jonathan D. (Physica. D, 2025)
Ejecta physics plays an important role in material interfaces that are impacted by a strong shock wave. When a shock impacts a rough surface of solid material and melts it, the Richtmyer–Meshkov instability grows perturbations on the surface, which can eject particles. After release, the ejecta travel through the post-shock compressible flow. To accurately simulate a large number of ejecta particles, an Euler–Lagrange approach is preferred, which requires modeling the subgrid-scale physics involved with fluid–particle interactions. We generalize the previous work from Hsiao et al. (2023) to consider systems of moving particles subject to any loading shock. The following improvements were made: (1) Particles are allowed to move relative to each other (2) Non-planar shocks are accounted for along with allowing for variable shock speeds. The generalized algorithm was tested with particle-resolved simulations for canonical test cases. The results of these tests are discussed and analyzed.